Predicting Metaethics of Nurses based on Moral Reasoning, Moral Behavior, and Mental Health: nurse’s moral reasoning, moral behavior and health with their moral metacognition - Ashoori, Jamal (Bioethics and Health Law Journal (BHL), 2021)
Background and Aim: Metaethics reflects knowledge of persons from moral nature, principles, and processes. Metaethics is effect by many variables such as moral reasoning, moral behavior, and mental health. The aimed to investigate the predicting metaethics of nurses based on moral reasoning, moral behavior, and mental health. Materials and Methods: This is a cross-sectional study of correlational type. The statistical population included all nurses of Varamin hospitals in 2016 years. Totally 90 nurses were selected through simple random sampling. All of them completed the questionnaires include metaethics, moral reasoning, moral behavior, and mental health. Data were analyzed using Pearson correlation and multivariate regression with stepwise model methods and with using SPSS-19 software. Ethical Considerations: In this study, verbal informed consent of participants was obtained followed by an explanation about the purpose of the study, anonymity, and confidentiality of patients’ information. Findings: The results showed a positive and significant relationship between moral reasoning, moral behavior, and mental health with metaethics of nurses. In a one-predicted model, moral behavior, mental health, and moral reasoning predicted 37/2 percent of the variance of metaethics among nurses (p≤0/01). Conclusion: According to findings, moral behavior, mental health, and moral reasoning were the most important predictors of metaethics of nurses. Therefore, it is suggested that planners and counselors consider the symptoms of these variables and design and Implement appropriate programs to improve the metaethics of nursing. *Corresponding Author: Jamal Ashoori; Email: jamal_ashoori@yahoo.com ; ORCID: https://orcid.org/0000-0001-5371-040X Please cite this article as: Ashoori J. Predicting Metaethics of Nurses based on Moral Reasoning, Moral Behavior and Mental Health. Bioeth Health Law J. 2021; 1:1-7: (e14). http://doi.org/10.22037/bhl.v1i1.38164